2016
DOI: 10.1186/s40104-016-0088-6
|View full text |Cite
|
Sign up to set email alerts
|

Single and double layer centrifugation improve the quality of cryopreserved bovine sperm from poor quality ejaculates

Abstract: BackgroundDensity gradient centrifugation was reported as a technique of semen preparation in assisted reproductive techniques in humans and animals. This technique was found to be efficient in improving semen quality after harmful techniques such as cryopreservation. Recently a modified technique, single layer centrifugation, was proposed as a technique providing a large amount of high quality spermatozoa, and this treatment was performed before conservation. Single layer centrifugation has been studied preva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
28
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 40 publications
4
28
1
Order By: Relevance
“…To carry out simultaneous measurements of MMP and ROS on the same aliquots, a different fluorochrome would be needed; this possibility is currently being investigated. In contrast, Gloria et al (2016) were unable to detect a change in MMP levels between selected and unselected sperm samples using iodixanol as the separation medium.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…To carry out simultaneous measurements of MMP and ROS on the same aliquots, a different fluorochrome would be needed; this possibility is currently being investigated. In contrast, Gloria et al (2016) were unable to detect a change in MMP levels between selected and unselected sperm samples using iodixanol as the separation medium.…”
Section: Discussionmentioning
confidence: 76%
“…In contrast, Gloria et al. () were unable to detect a change in MMP levels between selected and unselected sperm samples using iodixanol as the separation medium.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Other methods of sperm selection, such as the swimup method reduce the use of centrifugation, but this technique is still necessary to concentrate the sample. Studies report that high centrifugal forces often promote higher sperm recovery (WAITE et al, 2008;LEN et al, 2010;GLORIA et al, 2016) Some studies suggested that a reduction in the force and duration of centrifugation could reduce sperm damage and improve the sperm selection protocol using Percoll gradient (GUIMARÃES et al, 2014;KIM et al, 2013). However, these studies evaluated only the first centrifugation for sperm selection disregarding the second centrifugation for sperm concentration.…”
Section: Introductionmentioning
confidence: 99%